INVESTIGATING THE GAP OF ARBITRATION IN IRANIAN LAW - Palizban, Masuod; Jafarzadeh, Siamak; Sarnaghi, Reza Nikkhah (Gênero & Direito, 2019)
The existence of family disputes is influenced by the complicated social conditions and circumstances at present. If a dispute occurs between the couples, it is necessary that the government extirpate the source of dispute and make peace between the couples. In Iranian law, this institution is referred as arbitration. Arbitration is a Quranic solution for the settlement of family disputes and this Qur’anic verdict has been taken into consideration by the legislators and regulations were enacted in this regard. Differences in jurisprudential views and changing social conditions have caused changes in the current positive laws in the field of arbitration; however, there are shortcomings in this law. In this research, the arbitration principles, the evolution of legislation in arbitration, examining the current law of arbitration and explaining the legal defects in Iranian law are studied by the descriptive-analytical method. Finally, it is suggested that the judicial system along with the family courts constitutes the required numbers of arbitration branches comprised of legal experts, family counselors and a psychologist to help the court for settlement of family disputes.